2020
DOI: 10.1051/e3sconf/202015002003
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of Bacillussp. Gn-A11-18isolated from decomposing solid green household waste in water and soil against Candida albicans and Aspergillus niger

Abstract: Candida albicans an opportunistic pathogenic fungus causes many infections in humans. Whereas Aspergillus niger is a fungus that can produce ochratoxins, a group of extremely dangerous secondary metabolites that are classified as potentially carcinogenic to humans and also causing deterioration in grapes, strawberries, etc. The purpose of the current study is to isolate, purify, identify and characterize new microorganisms associated with solid green household waste for the control of C. albicans and A. niger.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 28 publications
(29 reference statements)
1
24
0
Order By: Relevance
“…These results are in agreement with investigated elsewhere [ 45 ], which showed that oil from Borojoa patinoi Cuatrec exhibited an inhibitory effect towards C. albicans since both share some common chemicals. Moreover, numerous studies place priority natural products especially essential oil for controlling fungal strains including F. oxysporum , A. niger , A. flavus, and C. albicans [ 26 ]. Several epidemiological studies have been conducted on yeast infections indicated that Candida is responsible for many diseases [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with investigated elsewhere [ 45 ], which showed that oil from Borojoa patinoi Cuatrec exhibited an inhibitory effect towards C. albicans since both share some common chemicals. Moreover, numerous studies place priority natural products especially essential oil for controlling fungal strains including F. oxysporum , A. niger , A. flavus, and C. albicans [ 26 ]. Several epidemiological studies have been conducted on yeast infections indicated that Candida is responsible for many diseases [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, Whatman paper disks (6 mm in diameter) impregnated with 10 μ L of essential oils were placed on the surface of Petri dishes before being incubated at 30°C in the darkness. The inhibition diameter, as well as inhibition percentage, was determined after 48 h of incubation for C. albicans and after 7 days for A. niger, A. flavus, and F. oxysporum [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…TPW, PPW and BPW have a relatively high microbial biodiversity [ 90 , 283 ]. Over the last few years, numerous research studies have focused on the recovery of microorganisms isolated from these wastes in the medical, agronomic and industrial fields.…”
Section: Tpw Ppw and Bpw Valorisation Methodsmentioning
confidence: 99%
“…Also, Maeno et al [ 289 ] have isolated Pseudofructophilic Leuconostoc citreum Strain F192-5 from TPW able to produce mainly lactate and acetate, with trace amounts of ethanol, from d -glucose metabolism. For PPW, El Barnossi et al [ 283 ] have isolated and identified a Bacillus sp. strain Gn-A11-18 from pomegranate waste that has shown a significant antifungal activity against Candida albicans and A. niger .…”
Section: Tpw Ppw and Bpw Valorisation Methodsmentioning
confidence: 99%
“…Wattman paper disks (6 mm in diameter) were deposited on the surface of the inoculated media and impregnated with 20 μL EOs extracted from M. recutita. 22 The inoculated petri dishes were incubated at 37 °C in the dark. The inhibition diameter was determined after 24 hrs of incubation.…”
Section: Disk Diffusion Methodsmentioning
confidence: 99%